Acetyl-CoA synthetase 2(ACSS2): a review with a focus on metabolism and tumor development - Rui Ling; Gong Chen; Xiang Tang; Na Liu; Yuepeng Zhou; Deyu Chen (Discover Oncology, 2022)
Abstract Acetyl-CoA synthetase 2 (ACSS2), an important member of the acetyl-CoA synthetase (ACSS) family, can catalyze the conversion of acetate to acetyl coenzyme A (acetyl-CoA). Currently, acetyl-CoA is considered an important intermediate metabolite in the metabolism of energy substrates. In addition, nutrients converge through acetyl-CoA into a common metabolic pathway, the tricarboxylic acid cycle and oxidative phosphorylation. Not only does ACSS2 play a crucial role in material energy metabolism, it is also involved in the regulation of various acetylation processes, such as regulation of histone and transcription factor acetylation. ACSS2-mediated regulation of acetylation is related to substance metabolism and tumorigenesis. In mammalian cells, ACSS2 utilizes intracellular acetate to synthesize acetyl-CoA, a step in the process of DNA and histone acetylation. In addition, studies in tumors have shown that cancer cells adapt to the growth conditions in the tumor microenvironment (TME) by activating or increasing the expression level of ACSS2 under metabolic stress. Therefore, this review mainly outlines the role of ACSS2 in substance metabolism and tumors and provides insights useful for investigating ACSS2 as a therapeutic target.